Functional panniculectomy vs cosmetic abdominoplasty: Multicenter analysis of risk factors and complications. Issue 9 (September 2022) - Kalmar, Christopher L.; Park, Benjamin C.; Kassis, Salam; Higdon, Kent K.; Perdikis, Galen
Summary: Background: Amidst the rising trend of bariatric surgical procedures being performed across the country and around the world, patients seeking functional panniculectomy after massive weight loss represent a different population than those seeking cosmetic abdominoplasty. The purpose of this study was to determine whether certain complications are more likely to occur in patients undergoing functional panniculectomy, as well as identify risk factors that are implicated in the occurrence of adverse events. Methods: Retrospective cohort study was conducted of patients undergoing cosmetic abdominoplasty and functional panniculectomy in North America between 2015 and 2019 using the National Surgical Quality Improvement Program database sponsored by the American College of Surgeons. Comorbidities and postoperative complications between these two cohorts were analyzed with appropriate statistics. Results: During the study interval, 11, 137 patients underwent excision of excessive infraumbilical abdominal skin, including 57.4% ( n  = 6397) patients undergoing functional panniculectomy and 42.6% ( n  = 4740) patients undergoing cosmetic abdominoplasty. Patients undergoing functional panniculectomy were significantly more likely to have comorbidities than those undergoing cosmetic abdominoplasty ( p  < .001). Overall adverse events ( p  < .001), medical complications ( p  = .047), surgical complications ( p  < .001), related readmission ( p  < .001), and related reoperation ( p  < .001) were significantly higher in patients undergoing functional panniculectomy. Surgical complications significantly higher in functional panniculectomy included superficial incisional infection ( p  < .001), deep incisional infection ( p  < .001), organ/space infection ( p  < .001), dehiscence ( p  = .003), and bleeding requiring transfusion ( p  = .003). Conclusions: Patients undergoing functional panniculectomy are significantly more likely to have comorbidities and experience postoperative wound infection, dehiscence, sepsis, bleeding, related readmission, and related reoperation.